KEGIATAN MAGANG PROGRAM DU/DI DI BAGIAN OPS PENYIMPANAN DAN PENGELUARAN - Muhammad Hukmi (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The internship program in the Business and Industrial World (DU/DI) is a form of practical learning aimed at improving students’ competencies according to workplace demands. This study aims to describe the implementation of internship activities in the OPS storage and goods issuing section of a logistics company and to analyze the effectiveness of the operational system applied. This research used a qualitative descriptive method with data collection techniques including observation, informal interviews, and documentation during the internship activities. The results showed that the goods storage system had implemented the FIFO (First In First Out) method with a compliance rate of 92%, which helped maintain proper goods rotation. The application of a barcode system in stock recording also increased inventory accuracy up to 95%. In addition, the timeliness of goods issuing reached 92%, while warehouse arrangement activities achieved 90%. The obstacles encountered mainly originated from internet network disruptions and limited scanner devices that affected operational efficiency. Overall, the internship activities provided students with real experience in understanding logistics systems and warehouse management, as well as improving technical competencies and soft skills needed in the industrial world.